Environmental-Oriented Tourism Development and Legal Governance in Indonesia - I Gusti Made Andrian Sumantri (Bali Tourism Board, 2025)
Tourism acts as an essential sector in Indonesia’s national development, making substantial contributions to economic growth, employment generation, and regional income. Nevertheless, the rapid expansion of tourism activities has resulted in major environmental degradation, social inequality, and governance challenges. This study investigates tourism development from an environmentally oriented legal perspective, stressing the necessity of sustainable tourism governance rooted in environmental protection, legal compliance, and social responsibility. Employing a normative juridical research method, the article analyses Indonesian legal instruments governing tourism and environmental protection, including statutory regulations, doctrinal principles, and relevant scholarly literature. The results show that, although Indonesia has established comprehensive legal documents to regulate environmentally sustainable tourism, implementation remains weak due to policy voids, limited control procedures insufficient integration of local wisdom and community participation. Strengthening environmental law enforcement, clarifying corporate social and environmental obligation recognising the roles of indigenous and local communities are fundamental for guaranteeing sustainable tourism. This analysis develops the discussion on sustainable tourism law by emphasising the need for transformative legal governance that aligns with economic interests, ecosystem protection, and social justice.